Electromagnetic modes of a coaxial plasma waveguide in an external magnetic field - Karas, I.V.; Zagrebelny, I.A. (Вопросы атомной науки и техники, 2015)
For carrying out of the further numerical comparisons with experimental researches on breakdown of a mixture of gases by microwave radiation with a stoсhastic jumping phase the theoretical researches of wave dispersive properties of the coaxial waveguide are carried out. Electromagnetic modes of a coaxial plasma waveguide in an external magnetic field are investigated. The existence of quasi-TEM modes in a finite-strength magnetic field is demonstrated. It is shown that, in the limits of infinitely strong and zero magnetic fields, this mode transforms into a true TEM mode. Для проведення подальших кількісних порівнянь з експериментальними дослідженнями з пробою суміші газів за допомогою мікрохвильового випромінювання зі стохастичними стрибками фази проведені детальні теоретичні дослідження дисперсійних властивостей плазмового коаксіального хвилеводу. Досліджені електромагнітні хвилі, що поширюються в коаксіальному плазмовому хвилеводі, який вміщено в зовнішнє магнітне поле. Продемонстрована наявність режимів квазі ТЕМ-типу хвиль у магнітному полі скінченної величини. Показано, що в межах нескінченно сильного та нульового магнітних полів існують ТЕМ-типу хвилі. Для проведения дальнейших численных сравнений с экспериментальными исследованиями по пробою смеси газов с помощью микроволнового излучения со стохастическими скачками фазы проведены детальные теоретические исследования дисперсионных свойств плазменного коаксиального волновода. Исследованы электромагнитные волны, распространяющиеся в коаксиальном плазменном волноводе, помещенном во внешнее магнитное поле. Продемонстрировано наличие режимов квази ТЕМ-типа волн в магнитном поле конечной величины. Показано, что в пределах бесконечно сильного и нулевого магнитных полей существуют ТЕМ-типа волны.